CAR-NK cells for cancer immunotherapy: recent advances and future directions - Li, Tianye; Niu, Mengke; Zhang, Weijiang; Qin, Shuang; Zhou, Jianwei; Yi, Ming (Frontiers in Immunology, 2024)
Natural Killer (NK) cells, intrinsic to the innate immune system, are pivotal in combating cancer due to their independent cytotoxic capabilities in antitumor immune response. Unlike predominant treatments that target T cell immunity, the limited success of T cell immunotherapy emphasizes the urgency for innovative approaches, with a spotlight on harnessing the potential of NK cells. Despite tumors adapting mechanisms to evade NK cell-induced cytotoxicity, there is optimism surrounding Chimeric Antigen Receptor (CAR) NK cells. This comprehensive review delves into the foundational features and recent breakthroughs in comprehending the dynamics of NK cells within the tumor microenvironment. It critically evaluates the potential applications and challenges associated with emerging CAR-NK cell therapeutic strategies, positioning them as promising tools in the evolving landscape of precision medicine. As research progresses, the unique attributes of CAR-NK cells offer a new avenue for therapeutic interventions, paving the way for a more effective and precise approach to cancer treatment.